Security Threats in Telecom Networks by Prompt Poisoning of MCP Servers and Mitigations - Binu Kiliamkavunkal Govindan (Journal of Computational Analysis and Applications (JoCAAA), 2026)
The communication sector experiences the most security challenges ever because artificial intelligenceagents are integrated into the network functioning, customer service, and administration. The use ofprompt poisoning and injection attacks is one of the critical vulnerabilities that can be used to put pressure on the AI systems in understanding instructions